THE RELATIONSHIP OF SELF-EFFICACY WITH WORK READINESS OF VOCATIONAL EDUCATION STUDENTS - Dwiki Muda Yulanto; Henry Iskandar; Liana Atika (Program Studi Pendidikan Teknik Mesin Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwiajaya, 2024)
Work readiness is the ability, skills and work attitudes that meet the demands of society and match the needs of the job. One of the factors in work readiness is related to a person's belief in their abilities or what is called self-efficacy. The aim of this research is to analyze the relationship between self-efficacy and work skills of final year students. This research is descriptive quantitative research using simple regression analysis techniques. The research results show a correlation coefficient of 0.591 and a significance level of <0.05, which means that self-efficacy has a significant relationship with work readiness. The level of contribution of self-efficacy to work readiness is 34.9%. The regression coefficient obtained was 0.476, which means that for every 1% increase in self-efficacy there is an increase in work readiness of 0.476. These figures show that self-efficacy has a positive effect on students' work readiness